Behavioral effects of MDMA (“Ecstasy”) on adult zebrafish - Stewart, Adam (2011)
3,4-Methylenedioxymethamphetamine (MDMA, “Ecstasy”) is a potent psychedelic drug inducing euphoria and hyper-sociability in humans, as well as hyperactivity and anxiety in rodents. Adult zebrafish (Danio rerio) have become a widely used species in neurobehavioral research. Here, we explore the effects of a wide range (0.25–120 mg/L) of acute MDMA doses on zebrafish behavior in the novel tank test. While MDMA was inactive at lower doses (0.25–10 mg/L), higher doses reduced bottom swimming and immobility (40–120 mg/L) and impaired intra-session habituation (10–120 mg/L). MDMA also elevated brain c-fos expression, collectively confirming the utility of zebrafish models for screening of hallucinogenic compounds.